The United Nations International Covenant on Economic, Social and Cultural Rights protection regime for migrants, refugees and refugees - Leão, Renato Zerbini Ribeiro (2019)
This article presents an analysis of the United Nations Committe on Economic, Social and Cultural Rights (CESCR) main production, seeking to demonstrate the solid regime of protection for migrants, refugees and asylum seekers emerging from the International Covenant on Economic, Social and Cultural Rights (ICESCR). The methodology consisted of document review plus the author's active individual participation in constructive dialogue with ICESCR States Parties, in the development, drafting, conclusion and official approval of this production embodied in official CESCR documents.